Reproductive Neuroendocrine Pathways of Social Behavior - Parhar, Ishwar S.; Ogawa, Satoshi; Ubuka, Takayoshi (Frontiers in Endocrinology, 2016)
Social behaviors are key components of reproduction because they are essential for successful fertilization. Social behaviors such as courtship, mating, and aggression are strongly associated with sex steroids, such as testosterone, estradiol and progesterone. Secretion of sex steroids from the gonads is regulated by the hypothalamus-pituitary-gonadal (HPG) axis in vertebrates. Gonadotropin-releasing hormone (GnRH) is a pivotal hypothalamic neuropeptide that stimulates gonadotropin release from the pituitary. In recent years, the role of neuropeptides containing the C-terminal Arg-Phe-NH2 (RFamide peptides) has been emphasized in vertebrate reproduction. In particular, two key RFamide peptides, kisspeptin and gonadotropin-inhibitory hormone (GnIH), emerged as critical accelerator and suppressor of gonadotropin secretion. Kisspeptin stimulates GnRH release by directly acting on GnRH neurons, whereas GnIH inhibits gonadotropin release by inhibiting kisspeptin or GnRH neurons or pituitary gonadotropes. These neuropeptides can regulate social behavior by regulating the HPG axis. However, distribution of neuronal fibers of GnRH, kisspeptin and GnIH neurons are not limited within the hypothalamus, and the existence of extra-hypothalamic neuronal fibers suggests direct control of social behavior within the brain. It has traditionally been shown that central administration of GnRH can stimulate female sexual behavior in rats. Recently, it was shown that Kiss1, one of the paralogs of kisspeptin peptide family, regulates fear responses in zebrafish and GnIH inhibits socio-sexual behavior in birds. Here we highlight recent findings regarding the role of GnRH, kisspeptin and GnIH in the regulation of social behaviors in fish, birds and mammals and discuss their importance in future biological and biomedical research.